2019
DOI: 10.1002/jcb.27949
|View full text |Cite
|
Sign up to set email alerts
|

2,3,5,4′‐Tetrahydroxystilbene‐2‐O‐β‐d‐glucoside eliminates ischemia/reperfusion injury–induced H9c2 cardiomyocytes apoptosis involving in Bcl‐2, Bax, caspase‐3, and Akt activation

Abstract: Objective: This study was designed to explore the protective effect of 2,3,5, 4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG) against ischemia/reperfusion (I/R) injury-induced cardiomyocytes apoptosis. Methods: The H9c2 cell I/R injury model was induced by simultaneous shortage of nutrients and oxygen. TSG administration (0.10, 0.25, and 0.50 mM) was performed before and during I/R stimulation. Cell apoptosis was evaluated using terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…The results showed that QLQX could significantly reduce the infarct area, improve the heart function and survival rate of mice at 28 days after surgery. Bcl-2-related protein family is the main regulator of cell apoptosis signal transduction pathway, and the ratio of anti-apoptosis protein Bcl-2 to pro-apoptosis protein Bax determines whether cells undergo apoptosis when stimulated by apoptosis signal [28,30]. Our study found that after ligation of left coronary artery, the expression of Bax increased significantly while the expression of Bcl-2 decreased significantly in MI + saline group compare to sham group.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The results showed that QLQX could significantly reduce the infarct area, improve the heart function and survival rate of mice at 28 days after surgery. Bcl-2-related protein family is the main regulator of cell apoptosis signal transduction pathway, and the ratio of anti-apoptosis protein Bcl-2 to pro-apoptosis protein Bax determines whether cells undergo apoptosis when stimulated by apoptosis signal [28,30]. Our study found that after ligation of left coronary artery, the expression of Bax increased significantly while the expression of Bcl-2 decreased significantly in MI + saline group compare to sham group.…”
Section: Discussionmentioning
confidence: 48%
“…Basic research shows that QLQX could restrain hypoxia-induced injury in primary rat cardiac microvascular endothelial cells via promoting glycolysis in a HIF-1a-dependent manner [27]. During hypoxia, cardiac microvascular endothelial cells (CMVECs) promote the expression of vascular endothelial growth factor (VEGF) and QLQX could attenuate this injury via facilitating hypoxia inducible factor-1α(HIF-1α)dependent glycolysis [28]. However, the mechanism of QLQX on apoptosis still remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Stilbenes, mainly 2,3,5,4′-tetrahydroxystilbene-2-O-β-D-glucoside (TSG), possessed antioxidative, antitumor, anti-inflammatory, endothelial protective, neuroprotective, and liver-protective activities, etc. [10][11][12][13][14][15][16][17][18][19][20][21]. Anthraquinones were reported to possess many biological activities, including immunomodulating, anticancer, antimutation, antibacterial, anticancer, antioxidant, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Bcl-2 is a famous representative suppressor of apoptosis, while Bax can combine with Bcl-2 to form a heterodimer for antagonize the inhibitory effect of Bcl-2 on apoptosis and promote apoptosis [41]. On the other hand, Bax also activates caspase-3 with promoting the Ca 2+ release and then causes cell apoptosis [42]. Caspase-3 is as a representative executor plays a pivotal role in cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%